2000
DOI: 10.1002/(sici)1099-0518(20000101)38:1<90::aid-pola12>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitization of carbazole derivatives in cationic polymerization with a novel sensitivity to near‐UV light

Abstract: Photosensitizers based on the carbazole structure were designed and developed for cationic polymerization. Along with triarylsulfonium and diaryliodonium salts, the carbazole derivatives showed a high photosensitization effect in the cationic photopolymerization of epoxides. The photophysical properties of the carbazole derivatives were studied in terms of electronic absorption, fluorescence, and phosphorescence spectrometry. Moreover, a unique photosensitization mechanism of the carbazole derivatives was disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Phenothiazine and its derivatives are another class of efficient photosensitizers with excellent reducing properties. In a similar manner, thioxanthones, carbazoles, curcumin, , quinoxaline and related structures, and highly conjugated derivatives of thiophene , have been used as long wavelength photosensitizers. Moreover, several other studies have been reported on photosensitization of onium salts based on photoinduced electron transfer reactions for the initiation of cationic polymerization. , It was recently shown that ferrocenium salts can promote sensitization of onium salts via photoinduced electron transfer .…”
Section: Photoinitiation Of Chain Polymerization By Photoinduced Elec...mentioning
confidence: 99%
“…Phenothiazine and its derivatives are another class of efficient photosensitizers with excellent reducing properties. In a similar manner, thioxanthones, carbazoles, curcumin, , quinoxaline and related structures, and highly conjugated derivatives of thiophene , have been used as long wavelength photosensitizers. Moreover, several other studies have been reported on photosensitization of onium salts based on photoinduced electron transfer reactions for the initiation of cationic polymerization. , It was recently shown that ferrocenium salts can promote sensitization of onium salts via photoinduced electron transfer .…”
Section: Photoinitiation Of Chain Polymerization By Photoinduced Elec...mentioning
confidence: 99%
“…Indeed, camphorquinone/amine systems are another category of dual-component photoinitiator that provides chemical amplification and rapid polymerization , and can often be quite efficient. Yet, the oxidation of free radicals by onium salts, as in the case of CQ/OPPI, is an elegant and relatively flexible type of initiation for free radical as well as cationic polymerization and has thus garnered significant attention. ,, Hence, we selected the CQ/OPPI system owing to its effectiveness in the photopolymerization of acrylate systems , successful use in self-trapping in our previous studies as well as for the future opportunity to examine growth in cationic systems.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Higher anionic dimension leads to lower nucleophilicity, and photogeneration of stronger acids. Therefore, even if the anions have no direct role in the photochemistry, their structural dimensions strongly influence the polymerization kinetics [ 32 , 33 ].…”
Section: Cationic Uv-curingmentioning
confidence: 99%